The Berenstain Bears get their kicks - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1998)
When Brother and Sister try out for soccer teams, Papa is at first disappointed that they do not want to play baseball, but he changes his mind when he sees them practice.